Modalities of endovascular management for internal iliac artery aneurysms. Issue 11 (30th September 2021) - Chen, Reuben J.; Vaes, Roel H. D.; Qi, Sara D.; J. Westcott, Mark; Robinson, Domenic R.
Abstract: Background: Internal iliac artery aneurysms (IIAA) are uncommon. Open repair is technically challenging and has been associated with increased morbidity and mortality compared with repair of abdominal aortic aneurysms. The aim of this study is to assess the outcomes of endovascular treatment of IIAA and incidence of postoperative pelvic ischaemia. Methods: A single‐centre retrospective analysis was performed for IIAAs treated with endovascular repair between January 2005 and December 2017. Aneurysm morphology, mode of presentation and operative technique were evaluated. Primary outcomes were 30‐day mortality and incidence of pelvic ischaemia. Secondary outcomes were technical success, major complications and reintervention. Results: Twenty‐nine IIAAs were treated in 23 patients with a mean age of 74 */‐ 9 years. Six patients had isolated IIAAs (26%); the remaining 17 patients had aortoiliac aneurysms. Five patients (22%) required emergent repair for ruptured IIAAs. Mean IIAA size was 4.1 cm */‐ 1.8 and ruptures occurred at mean 6.1 cm */‐ 2.6. Endovascular techniques used: stent graft occlusion of the internal iliac artery (IIA) ostium ( n = 16), deployment of iliac branch device ( n = 9), and other endovascular techniques ( n = 4). The 30‐day mortality was zero. Three patients (13%) experienced post‐operative pelvic ischemia which were all minor chronic gluteal claudication after IIA occlusion. Primary technical success was achieved in 27 repairs (93%). There was one late reintervention (3%). Conclusion: IIAAs are often asymptomatic and diagnosed incidentally, however, a significant proportion present emergently. Endovascular treatment is feasible for both ruptured and non‐ruptured aneurysms with low perioperative morbidity, mortality and reintervention rates. Abstract : We conducted a risk‐scoring model to predict multiple synchronous gastric neoplasms (MSGN) before initial endoscopic resection (ER). The model was internally validated to have a good performance in predicting MSGN. Multicenter studies with large samples are warranted to confirm our findings.